A method for fabricating stainless steel pellets with open-cell porosity by alkaline leaching of silica template - Covaciu, M; Richter, E; Walczak, M; Jin-Chong, T; del Valle, J (Wiley, 2016)
In this paper, a method of fabricating metallic analogues of biological materials is presented. In particular, the structure of pre-pressed oilseed used for physical modeling of supercritical CO2 extraction of desired substances is replicated in a material commonly used for manipulation of foods, i.e. food grade stainless steel (AISI 316L). Powder metallurgy approach is employed through sintering the steel powder with SiO2 spacer and further leaching the porogen. The resulting metal framework has interconnected porosity and low apparent density (about 1.91 g/cm^3). The prospect of tuning the balance between porosity and interconnectivity of pores is of special concern to allow mimicking the structure of natural materials intended for supercritical CO2 extraction. With this motivation, the effects of initial silica content (between 20 to 60 vol.%) and silica particle size (small: 0.5-10 µm, medium: 110 µm, and large: 170-630 µm) on the structural and mechanical properties of the porous material are studied. It is found that increasing porosity correlates with decreasing compressive strength, whereas the plateau region of the stress-strain relationship in compression is of lower slope and spans over larger strain. Yield strength ranges from 4.2 MPa to 220 MPa, which is sufficient for sustaining the conditions of supercritical extraction.